Investigation of the effects of the impeller blades and vane blades on the CAP1400 nuclear coolant pump's performances with a united optimal design technology. (August 2020) - Lu, Yeming; Wang, Xiaofang; Liu, Haoran; Li, Yingyue
Abstract: Known as the "heart of the nuclear island, " the nuclear coolant pump of the CAP1400 nuclear power unit is the only device that cannot be manufactured domestically (in China). Nevertheless, the rotating impeller and the static vane are the most important flow passage components. The efficiency and head, the pressure pulsation, the radial forces, and the axial forces are the main performance factors of operating stability in a coolant pump. To evaluate the effects of the impeller blades and the vane blades on the above performance factors, a united optimal design technology comprised of a constrained shape design methodology, the CFD analysis, the LHS method, the predicting model, and the MOPSO algorithm was proposed. Taking the 1:2.5 scaled hydraulic model with a relatively-high performance as the target, three groups of optimized impeller blades and vane blades were obtained. A comparative analysis led to the following conclusions: the optimized impeller blades and the optimized vane blades can both improve the pump's efficiency, head, and axial forces; the optimized vane blades can decrease almost all of the monitoring pressure pulsation's amplitudes in the coolant pump, but the optimized impeller blades can only improve the amplitudes in the impeller domain; the optimized vane blades can greatly decrease the radial forces, however, the optimized impeller blades do not seem to have any clear effect on the radial forces; relative to the optimized vane blades, the impeller blades can produce a wider change in the axial force. Graphical abstract: Image 1 Highlights: A united shape design methodology for the impeller blade and the vane blade is proposed. A united optimal design technology designing out the multiple and superior impeller blades and vane blades is proposed. The effects of the optimized impeller blades and vanes blades on the CAP1400 nuclear coolant pump's performances are illustrated.